The relationship between pregnancy stress and antepartum depression in Chinese pregnant women: the mediating effect of social support and maternal health literacy - Zhang, Ling; Wu, Fanghui; Li, Fengju; Feng, Xinyi; Yang, Hong; Zhou, Tao; Rong, Honghui; Zheng, Chuanfen; Luo, Ting; Lu, Lu; Lei, Enyu; Deng, Guangxu; et al. (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to explore the relationship between pregnancy stress (PS) and antenatal depression (AD) among Chinese pregnant women and to investigate whether maternal health literacy (MHL) and social support (SS) mediate the relationship between PS and AD.MethodThis cross-sectional study utilized a two-stage sampling approach, combining stratified random cluster sampling in the first stage with convenience sampling in the second stage, to enroll 1,391 pregnant women attending prenatal care at six hospitals in Chongqing between September 2023 and February 2024. Data were collected using structured scales, including general information questionnaire, Edinburgh Postnatal Depression Scale(EPDS), Pregnancy Stress Scale(PSS), Multidimensional Scale of Perceived Social Support(MSPSS) and Maternal health literacy questionnaire. We utilized Amos 22.0 to establish a structural equation model(SEM).Results443 participants (31.85%) reported symptoms of depression, and 382 participants (27.46%) had moderate or above stress; in contrast, only 82 participants (5.90%) reached the level of MHL. Spearman correlation analysis revealed that all the variables were significantly correlated with AD (p < 0.01). SEM revealed several effects on AD, including PS (β = 0.470, p < 0.01), SS (β = -0.257, p < 0.01) and MHL (β = -0.095, p < 0.01), all of which were associated with higher depression scores. SS and MHL mediated the link between PS and AD. MHL and SS exerted a negative influence on PS (β =−0.236, -0.289; p < 0.01). There was no evidence of a mediating effect of MHL on the relationship between SS and AD.ConclusionPS, SS and MHL have a direct effect on AD. Moreover, MHL and SS play a mediating role between PS and AD. Health care providers should be aware of the potential threat of PS progressing to AD. Under the guidance of the principles of enhancing MHL and strengthening SS, in the short term, the focus should be on improving the MHL among Chinese population.